How knowledge links with universities may foster innovation: The case of a science park. (April 2016) - Díez-Vial, Isabel; Montoro-Sánchez, Ángeles
Abstract: The objective of this research is to evaluate how technological knowledge flows from universities may increase innovation by firms located in a science park. We propose that firms with the capacity to acquire and assimilate the knowledge provided by universities, mainly due to being academic spin-offs or having long-term relationships with them, receive more knowledge from universities. We also argue that firms located in central positions inside the local firm-network have access to a complementary source of technical knowledge. Empirical evidence gathered from the Madrid Science Park confirms that having long-term relationships with universities, based on both formal and informal interactions, is the most important means of obtaining technical knowledge from them. We also observed a positive relationship between the technological knowledge obtained from universities and the innovation carried out by firms. Finally, we confirmed that firms with a significant role as intermediaries between other co-located firms have a higher level of innovation even if they are not involved in relationships with the university.